Utilizing Augmented Reality Media to Enhance Students’ Motivation and Spatial Thinking in 3D Geometry Learning - Saputra, Moch Panji Agung; Hidayana, Rizki Apriva; Azahra, Astrid Sulistya (Research Collaboration Community (Rescollacom), 2025)
This study explores the effectiveness of Augmented Reality (AR) learning media to improve students' spatial ability and learning motivation in spatial building material. In the era of digital transformation of education, AR offers interactive 3D visualization that is crucial for understanding abstract concepts and manipulating objects virtually. This quasi-experimental study used a pretest-posttest control group design on 60 junior high school students, with spatial ability test instruments and ARCS motivation questionnaires. The results showed a significant increase in the spatial ability of the experimental group (AR) with an average difference of +27.07 points and Cohen's d 1.82 (very large effect), far exceeding the control group (+15.06 points). All dimensions of student learning motivation also increased significantly in the AR group, with a total average of 84.67 and Cohen's d 1.45 (large effect), overcoming the boredom of conventional learning. This increase was due to the interactivity, visual aesthetics, and immersive experience of AR that supports embodied cognition. It was concluded that AR media is very effective in improving students' spatial competence and active engagement, making it a meaningful innovative learning tool.